2016
DOI: 10.1039/c6cy00559d
|View full text |Cite
|
Sign up to set email alerts
|

A combined theoretical and experimental EXAFS study of the structure and dynamics of Au147 nanoparticles

Abstract: We demonstrated the capability of combined EXAFS and DFT calculations for characterizing the structural and thermal properties of Au147 clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…For EXAFS data interpretation, MC simulations with empirical potential were recently employed by Duan and coworkers (38,41) to simulate EXAFS spectra in a heterogeneous system consisting of a mixture of pure Rh particles and bimetallic RhAu nanoparticles. Another MCrelated approach for simulation of EXAFS spectra was proposed by Duan and colleagues (32,44) for simulations of Au and Au Pt nanoparticles. In this case, DFT simulations were used to calculate a dynamical matrix and derive from it harmonic force constants and normal vibrational modes.…”
Section: Monte Carlo Simulations For Extended X-ray Absorption Fine Smentioning
confidence: 99%
See 1 more Smart Citation
“…For EXAFS data interpretation, MC simulations with empirical potential were recently employed by Duan and coworkers (38,41) to simulate EXAFS spectra in a heterogeneous system consisting of a mixture of pure Rh particles and bimetallic RhAu nanoparticles. Another MCrelated approach for simulation of EXAFS spectra was proposed by Duan and colleagues (32,44) for simulations of Au and Au Pt nanoparticles. In this case, DFT simulations were used to calculate a dynamical matrix and derive from it harmonic force constants and normal vibrational modes.…”
Section: Monte Carlo Simulations For Extended X-ray Absorption Fine Smentioning
confidence: 99%
“…To summarize, atomic-scale simulation of nanomaterial structure, guided by XAS data, is a new and rapidly developing field. The importance of and growing interest in such studies are supported by a number of recent publications devoted to this topic (15,17,19,26,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The approaches described in these articles often rely on similar ideas, but their implementation varies because such combined studies are still a relatively new tool for modeling NP structure.…”
Section: Introductionmentioning
confidence: 99%
“…Au 147 is one of the magic number clusters, and therefore the most stable structure assumed for it is an icosahedron. 20,23,24 We have generated a large number of isomers of Au 147 , and the structural pattern they follow is 105 atoms in the outer shell, 35 atoms in the middle shell, and 7 atoms in the inner shell, unlike an icosahedron that contains 13 atoms in the inner shell, 42 atoms in the middle shell, and 92 atoms in the outer shell. According to the ANN, and verified from DFT, the GM contains a 7-atom symmetric inner core structure, with the arrangement of the 35 atoms in the middle layer, also in a symmetric manner.…”
Section: A Global Optimization Of Au 147 Clustermentioning
confidence: 99%
“…The assumed geometry of these clusters is icosahedron which has been recently published by Li et al 20 In this work, we have applied our potential to analyse the dynamics of Au 147 . By performing an EXAFS study 23,24 on bare and supported Au 147 , it has been recently shown that Au 147 exhibits an icosahedron geometry since the fitted parameters match with an icosahedron geometry. We have found that although being a magic cluster, Au 147 does not exhibit an icosahedron geometry.…”
Section: Introductionmentioning
confidence: 99%
“…2014);House et al (2017)) or atomic displacement parameters obtained from lattice dynamics calculations(Duan et al (2016);Lapp et al (2018)). …”
mentioning
confidence: 99%